2011
DOI: 10.1111/j.1538-7836.2011.04541.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high‐density lipoprotein and paraoxonase‐1 on platelet reactivity in patients with acute coronary syndromes receiving clopidogrel therapy

Abstract: To cite this article: Tselepis AD, Tsoumani ME, Kalantzi KI, Dimitriou AA, Tellis CC, Goudevenos IA. Influence of high-density lipoprotein and paraoxonase-1 on platelet reactivity in patients with acute coronary syndromes receiving clopidogrel therapy. J Thromb Haemost 2011; 9: 2371-8.Summary. Background: The paraoxonase activity of the enzyme paraoxonase-1 (PON-1) associated with high-density lipoprotein (HDL) may significantly influence clopidogrelÕs antiplatelet and clinical efficacy as a result of its invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 42 publications
(63 reference statements)
2
26
0
Order By: Relevance
“…[14] and most subsequent studies are unclear. Differences in populations may be an issue; indeed, the frequency of the Q192 allele is somewhat lower in their cohort study (63.9%) than in any of the other studies [12,15–17,25–33,42]. A recent in vitro study by Dansette et al.…”
Section: Discussionmentioning
confidence: 84%
“…[14] and most subsequent studies are unclear. Differences in populations may be an issue; indeed, the frequency of the Q192 allele is somewhat lower in their cohort study (63.9%) than in any of the other studies [12,15–17,25–33,42]. A recent in vitro study by Dansette et al.…”
Section: Discussionmentioning
confidence: 84%
“…They also highlighted that individuals carrying the QQ isoform of PON1 192 gene polymorphism have a higher risk of stent thrombosis. Tselepis et al [5] showed an inverse association between PON-1 activity and platelet activation following clopidogrel administration, and suggested that PON-1 is an important determinant of clopidogrel antiplatelet efficacy in these patients. Dansette et al [6] reported that PON1 catalyzes the formation of a minor thiol metabolite, while the biosynthesis of the major clopidogrel metabolite is CYP P450 dependent.…”
Section: Introductionmentioning
confidence: 99%
“…There were no significantly differences in the three pharmacodynamic parameters, AUEC 0e24h , E max and E min of clopidogrel response observed among subjects with homozygous wild-type and heterozygous CYP2C19*2 genotypes who carried different PON1 genotypes. It should be noted that in the previous studies they did not take into account the different CYP2C19 genotypes among the subjects with different PON1 genotypes and thus these differences may influence the real impact of PON1 genetic polymorphism reported [16,17].…”
Section: Discussionmentioning
confidence: 89%
“…It has been demonstrated in some studies that individuals with the QQ192 genotype of PON1 have lower PON1 plasma activity, lower plasma concentrations of clopidogrel active metabolites and lower platelet inhibition as well as a higher risk of stent thrombosis compared to the individuals with RR192 genotypes [16,17], however, these results could not be confirmed in several studies [8,9]. The present results revealed that neither platelet inhibition measured by both the whole blood impedance aggregometry and the VerifyNow ® P2Y12 assays of subjects with different PON1 Q192R genotypes were significantly different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation